The Role of Renewable Energy Investment on Achieving Economic Growth at the Gulf Cooperation Council Countries - Jaradat, Mohammad Sulieman Mohammad (International Journal of Energy Economics and Policy, 2022)
Study aims to investigate the renewable energy investment effect on achieving the economic growth (EG) at countries of Gulf Cooperation Council (GCC) for the period of 2010–2019. The percentage of renewable energy investment of total investments is an explanatory variable, and EG is a dependent variable. This research focuses on analyzing literature review to demonstrate how investment in renewable energy impacts the achievement of EG, and it also tries to explain this effect in the GCC countries for this period by utilizing Regression Analysis in E-Views. The research reaches significant and positive effect of renewable energy investment on EG at UAE, KSA, and Qatar but showed insignificant effect of renewable energy investment on EG in Bahrain, Kuwait, and Oman for the period (2010–2019).